Adenomatoid odontogenic tumor: As an unusual mandibular manifestation - Neeraj Sharma; Sidhi Passi; Vinay V Kumar (Wolters Kluwer Medknow Publications, 2012)
Adenomatoid odontogenic tumor (AOT) is a rare odontogenic tumor which is often misdiagnosed as odontogenic cyst and accounts for about 1% until 9% of all odontogenic tumors. It is predominantly found in young and female patients, located more often in the maxilla in most cases associated with an unerupted permanent tooth. It is a benign (hamartomatous), noninvasive lesion with slow but progressive growth. There are three variants of AOT: follicular, extrafollicular, and peripheral. We report a rare case of follicular-type AOT in the mandible of a 14-year-old male patient who presented with right -sided jaw swelling.